Absorção de carbono em um manguezal no sudeste do Brasil: perspectiva de análise dos serviços ecossistêmicos - Pascoalini, Savia Soares (2019)
Mangroves are highly productive systems and represent important carbon sinks. Due to the structural and functional variability of the ecosystem the present work aims to describe the carbon absorption in peri-urban mangrove and its maintenance based on the structural analysis, carbon storage in the form of aerial biomass and photosynthesis. The work was developed in the mangrove of the Estuarine System of Greater Vitória (ESGV) in fringe and basin forests distributed throughout this environment. The thesis is composed by four chapters, the first evaluates the structural diversity of the mangrove, submitted to tensors considering the mortality, reflection of the forest degradation and the dominance of species, há important factor in the structure of the ecosystem. There was structural variability between the evaluated stations and differences in the species composition. The distribution of species occurs according to their ecological optimum, mainly in terms of organic matter (OM) concentration in the sediment and salinity for both Laguncularia racemosa (L.) Gaertn and Rhizophora mangle L. The second chapter evaluated the diametric distribution by means of probabilistic density functions. The Lognormal function described the diameter distribution of the physiographic types, the seasons and 59% of the plots, indicating continuous maintenance of the forests. The Weibull function suggested fragility of the forests and the species it describes (L. racemosa), in addition to maturity. Avicennia schaueriana Stapf & Leechman ex Moldenke is vulnerable to the situations imposed by virtue of the location of its colonization. The Gamma function described sites with structural development from intermediate to mature under antropic pressure. The third chapter deals with the ecophysiological plasticity of Rhizophora mangle and some of its controlling factors, it is observed that MO and the availability of incident radiation and, in a lower degree, salinity act on photosynthesis. The OM contributed to a better performance of the energy flux related to the electron transport, the results obtained indicate that the active photosynthetic radiation available mainly works on the fluorescence variables. Regarding salinity, there is negative damage to the reaction centers, but the species’ plasticity in relation to salt can be evidenced by the increase in carbon assimilation and the conservative use of water. As for the biotic factors controlling the photosynthetic efficiency, the chlorophyll a affects the performance of plants at the level of electron transfer and the PITotal was related to photosynthetic assimilation and to the conservative use of water. The last chapter evaluates the distribution of the carbon stored in the trees and verifies the maintenance possibilities in each evaluated forest. ESGV’s mangroves store on 80.0 ton. ha-1 carbon, comparable to other regions of the world known for the large amount of carbon stored in the vegetation. The carbon stock was associated with organic matter (R = 0.43, p = < 0.05). It is argued that the maintenance of this stock depends on the biological characteristics of the species that colonize the areas and the abiotic conditions of the system on a local and regional scale. The results obtained reinforce the importance of public management for the conservation of this ecosystem at the landscape level in view of the economic benefit provided by the mangrove ecosystem when performing the ecosystemic service of atmospheric carbon absorption.